2019
DOI: 10.1088/1361-6501/ab0afc
|View full text |Cite
|
Sign up to set email alerts
|

Determining the pressure distribution of a multi-phase flow through a pore space using velocity measurement and shape analysis

Abstract: Pore-scale velocity measurements can be achieved by using micro particle shadow velocimetry (µ-PSV). Characteristic properties of a flow are, however, best investigated and described by the pressure distribution in the field. At the pore scale, applying direct pressure measurement techniques comes with significant challenges. By detailed measurement of velocity and applying theoretical relations that suit the flow field under study, the pressure field can be determined. This study demonstrates the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Numerical simulation of a drop falling through a pore due to gravity in an ambient continuous liquid phase is conducted and the results are in qualitatively good agreement compared to the experimental data of Ansari et al (2018Ansari et al ( , 2019. In addition, quantitative verifications confirmed that the pressure distribution inside the deforming drop is consistent with the drop shape as it passes through the pore.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Numerical simulation of a drop falling through a pore due to gravity in an ambient continuous liquid phase is conducted and the results are in qualitatively good agreement compared to the experimental data of Ansari et al (2018Ansari et al ( , 2019. In addition, quantitative verifications confirmed that the pressure distribution inside the deforming drop is consistent with the drop shape as it passes through the pore.…”
Section: Discussionsupporting
confidence: 70%
“…The results are presented in two parts. First, we consider a drop falling through a pore due to gravity in the ambient continuous liquid phase and compare our results to the experimental data of Ansari et al (2018Ansari et al ( , 2019. This comparison is done for the purpose of qualitatively validating our model.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, studying oil–water two-phase flow with high water cut and low flow velocity, particularly in a horizontal small-diameter pipe, is necessary and timely. Velocity measurements of oil–water two-phase flow may be performed by various methods, including the ultrasonic method [9,10,11], the conductance method [12,13], the capacitance method [14,15,16], the electromagnetic method [17], the thermal tracer method, the optical fiber method, the capacitance resistance tomography method [18], the ultraviolet fluorescence [19,20], and particle image velocimetry (PIV) [21,22,23,24]. PIV has become an important research method because of its field visualization capability [25,26].…”
Section: Introductionmentioning
confidence: 99%